ANATOMI GERAKAN SOSIAL DI RIAU: Refleksi Atas Dinamika Perlawanan Masyarakat Riau terhadap Negara 1998 – 2001 - Hasanudin Hasanudin (Jurnal Sosiologi Reflektif, 2014)
A social movement is a collective opposing way established by plenty of communitiesl which have the same goals and aspirations in terms with a continuity interaction with the state. A social movement is a way considered effective in gaining the goal by mobilizing the supports and the resources, both economic or political resources. The success of a social movement is supported by a leadership factor in that movement and movement organisation by determining effective ways to get the collective goals. A social movement in a society is a manifestation from unsatisfaction toward the central goverment and natural resources exploitation or the economy of Riau people without taking notice of the existention and the continuity of Riau local people